If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 2) + -1(4n + 3) = 0 Reorder the terms: 5(2 + x) + -1(4n + 3) = 0 (2 * 5 + x * 5) + -1(4n + 3) = 0 (10 + 5x) + -1(4n + 3) = 0 Reorder the terms: 10 + 5x + -1(3 + 4n) = 0 10 + 5x + (3 * -1 + 4n * -1) = 0 10 + 5x + (-3 + -4n) = 0 Reorder the terms: 10 + -3 + -4n + 5x = 0 Combine like terms: 10 + -3 = 7 7 + -4n + 5x = 0 Solving 7 + -4n + 5x = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -4n + -7 + 5x = 0 + -7 Reorder the terms: 7 + -7 + -4n + 5x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4n + 5x = 0 + -7 -4n + 5x = 0 + -7 Combine like terms: 0 + -7 = -7 -4n + 5x = -7 Add '-5x' to each side of the equation. -4n + 5x + -5x = -7 + -5x Combine like terms: 5x + -5x = 0 -4n + 0 = -7 + -5x -4n = -7 + -5x Divide each side by '-4'. n = 1.75 + 1.25x Simplifying n = 1.75 + 1.25x
| 46x-63-25x=-174 | | 6/15=2/c= | | 1.25+x=2.5(2-x) | | x+1=30-x | | 2x^2-12x=10 | | 3xn=6 | | S^3=24 | | 3xm+2xn= | | 4x^2-17x-108=0 | | -14=25-3x | | -3=1x | | 7(-a-3)+5a+6= | | 9-9.45=-10.6 | | -3.3x+9.2=.5x-30.8 | | -2y-3=5y+18 | | 5x+14=120 | | 14(x+5)=120 | | -2x-5(6x+7)=-227 | | 2s-11=13+5s | | .7(x+200)=.76x-310 | | 3s-26=-36+8s | | 5x+y-3x+2y= | | c=0.4*285.7+100 | | 3/10x-3=1/5x | | (7+y)(4y+9)=0 | | -2(x+2)=3(x-2)+5 | | x+(x-54)=596 | | 6.3-0.9y= | | 3(x+4)=7x+4-4x+8 | | 7x-5y+3y= | | 2(1.25)+2x=24 | | 3+5(3x+-3)=5+8(4x+2) |